Priming of insulin granules for exocytosis by granular Cl(-) uptake and acidification. - Barg, S; Huang, P; Eliasson, L; Nelson, D; Obermüller, S; Rorsman, P; Thévenod, F; Renström, E (2001)
ATP-dependent priming of the secretory granules precedes Ca(2+)-regulated neuroendocrine secretion, but the exact nature of this reaction is not fully established in all secretory cell types. We have further investigated this reaction in the insulin-secreting pancreatic B-cell and demonstrate that granular acidification driven by a V-type H(+)-ATPase in the granular membrane is a decisive step in priming. This requires simultaneous Cl(-) uptake through granular ClC-3 Cl(-) channels. Accordingly, granule acidification and priming are inhibited by agents that prevent transgranular Cl(-) fluxes, such as 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid (DIDS) and an antibody against the ClC-3 channels, but accelerated by increases in the intracellular ATP:ADP ratio or addition of hypoglycemic sulfonylureas. We suggest that this might represent an important mechanism for metabolic regulation of Ca(2+)-dependent exocytosis that is also likely to be operational in other secretory cell types.